PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN PAPAN BISKUIT PECAHAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI OPERASI PECAHAN SEKOLAH DASAR: penelitian kuantitatif - Asti; Mariyam; Nindy Citroresmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to find out: 1) test the difference in students' understanding of mathematical concepts between classes using the CTL model assisted by fractional biscuit boards and classes that are given direct learning on fractional operation material. 2) to know student learning activities when learning is applied using the CTL model assisted by fractional biscuit boards with classes that are given a direct learning model on fractional operation materials. 3) to find out the students' response when learning is applied using the CTL model assisted by fractional biscuit boards with classes given a direct learning model on fractional operation materials. This type of research uses quantitative research. The design of this study is The Nonequivalent Posttest Only Control Group. The population of this study consists of 2 classes, namely classes IVA and IVB at SDS Torsina III Singkawang. The research sample was taken by probability sampling. The data analysis techniques with prerequisite tests carried out are normality tests, homogeneity tests, and T-Test Independent Sample Tests. The results of the study show that 1) There is a difference in students' ability to understand mathematical concepts between classes that are given the CTL model assisted by fractional biscuit boards and classes that use the direct learning model, namely with the Independent sample t-test score with a value of 0.003 < 0.005. 2) Student learning activities were classified as high after the implementation of the CTL model assisted by a fractional biscuit board with the average result of the presentation at two meetings by the validator, which was 79.40% of the high category. 3) The students' response was very good using the CTL model assisted by the class IVA fractional biscuit board at SDS Torsina III Singkawang was very high with the overall result of the student respondent questionnaire (83.02%).